Satisfaction in the teaching work in physical education: a diagnosis of the profile of university teachers - Caroline Broch; Jorge Both; Fabiane Castilho Teixeira; Juliana Pizani; Ieda Parra Barbosa-Rinaldi (Journal of Physical Education (Maringá), 2020)
The descriptive research had as objective to verify the different professor’s profiles of Physical Education, considering the satisfaction in the work and its relation with the sociodemographic and professional variables. We investigated 99 Physical Education college professors, with links in public and private institutions of Paraná. In the data collection, questionnaires were used to identify the sociodemographic profile and Quality of Life at Work. In the satistical analysis was used to Cluster analysis, Chi-square test and the Kruskal-Wallis test with post hoc Dunn's Multiple Comparison. The results showed three groups of college professors: Group 1 showed dissatisfaction, above all, with social integration and with work and total living space. Group 2 was dissatisfied with working conditions and social integration. And, Group 3 presented higher professional satisfaction, however, they had a shorter time in the university. Finally, we conclude that the socio-demographic and professional aspects are factors that intervene in the satisfaction with the professors job.